Sarcopenic Obesity and Endocrinal Adaptation with Age - Kunihiro Sakuma; Akihiko Yamaguchi (International Journal of Endocrinology)
In normal aging, changes in the body composition occur that result in a shift toward decreased muscle mass and increased fat mass. The loss of muscle mass that occurs with aging is termed sarcopenia and is an important cause of frailty, disability, and loss of independence in older adults. Age-related changes in the body composition as well as the increased prevalence of obesity determine a combination of excess weight and reduced muscle mass or strength, recently defined as sarcopenic obesity. Weight gain increases total/abdominal fat, which, in turn, elicits inflammation and fatty infiltration in muscle. Sarcopenic obesity appears to be linked with the upregulation of TNF-α, interleukin (IL)-6, leptin, and myostatin and the downregulation of adiponectin and IL-15. Multiple combined exercise and mild caloric restriction markedly attenuate the symptoms of sarcopenic obesity. Intriguingly, the inhibition of myostatin induced by gene manipulation or neutralizing antibody ameliorates sarcopenic obesity via increased skeletal muscle mass and improved glucose homeostasis. In this review, we describe the possible influence of endocrinal changes with age on sarcopenic obesity.